An observational study to evaluate weight gain of exclusively breastfed infants who feed only while sleeping - Mohammed, MTP; Khalid, Shahna (Indian Journal of Child Health, 2024)
Background: We encountered infants in our outpatient department (OPD) who have been breastfeeding normally till 3–6 months of age and stopped feeding while awake without any obvious reason, and continued feeding during sleep. This causes much anxiety and concern to the mother and demands intervention. Objectives: The aim of the study was to compare the weight gain of infants who breastfeed only during sleep, with babies who feed normally. Materials and Methods: An observational study has been carried out in pediatric OPD, at Government Medical College Kannur. Totally 30 breastfeeding mothers were interviewed and data were entered in a proforma. Weight gain was taken from the growth chart beginning from birth to 6 months. Results: Among the 30 breastfeeding mothers interviewed, 12 of them had infants who started feeding only during sleep from around 3 to 4 months of age. On the assessment of growth and development among these infants, it was noted that they were comparable with the infants on exclusive breastfeeding without the problem. No failure to thrive or delayed development was noted in the study group as compared to normal. Conclusion: Growth and development was normally attained in infants who breastfeed only while sleeping. As this matter hasn’t been studied anywhere so far and is a cause for anxiety in mothers, it demands further research and study.